Comparison of Wall Chair Exercises and Set Shoot Exercises on Basketball Free Throw Results - Alifya Ananda Pradana; Dewi Susilawati; Anggi Setia Lengkana (UNIB Press, 2024)
In this research, the researcher will focus on a problem, namely sports coaching, which greatly influences students' achievement at student level and the sport that the researcher focuses on in this research is basketball. In this research, the Upi Sumedang basketball UKM took part in the championship, namely PORSEMA, which was in Upi Bandung. At that time the researcher was a coach in the Sumedang Kamda team, during the semifinal between Sumedang Kamda and FPOK (Faculty of Sports and Health Education), there was a fierce match where the players from the teams Each of them has a sufficient athlete background and has had experience in PORDA (Regional Sports Week) but FPOK is also not inferior to several players who have been directly involved in POMNAS and LIMA (Student League) which can be said to be at the same level as national players. In the match, problems were found when playing for 4 quarters, Sumedang had the opportunity to get 12 free throws, but only got 1 of the 12 free throws or it could be said that it was only less than 10% of that percentage, so the researchers looked for and speculated on how the training was carried out. can increase the percentage of free throw shots. The method used in this research is experimental. This method was chosen because the main aim of this research is to determine the impact of a treatment. The research design used is